3D printing of resorbable poly(propylene fumarate) tissue engineering scaffolds. (12th February 2015) - Childers, Erin P.; Wang, Martha O.; Becker, Matthew L.; Fisher, John P.; Dean, David
Abstract: Abstract : Efficient, reproducible, and precise methodologies for fabricating tissue engineering (TE) scaffolds using three-dimensional (3D) printing techniques are evaluated. Fusion deposition modeling, laser sintering, and photo printing each have limitations, including the materials that can be used with each printing system. However, new and promising resorbable materials are surfacing as alternatives to previously studied resorbable TE materials for 3D printing. One such resorbable polymer is poly(propylene fumarate) (PPF), which can be printed using photocross-linking 3D printing. The ability to print new materials opens up TE to a wide range of possibilities not previously available. The ability to control precise geometries, porosity, degradation, and functionalities present on 3D printable polymers such as PPF shows a new layer of complexity available for the design and fabrication of TE scaffolds.